2011
DOI: 10.1590/s2176-94512011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Uma entrevista com James A. McNamara Jr.

Abstract: I met James A. McNamara Jr. in the late 70's when we both became full members of the Edward H. Angle Society of Orthodontists-Midwest. Jim is one of the most active members, always looking on to break boundaries with new works. During over 30 years, I saw him being presented with all the existing awards and honors in the field of orthodontics. Knowing his ability and persistence, I'm sure that if in the future other awards are instituted, Jim will be there to, with all merits, conquer them. It is fortunate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Occlusal acrylic splints are considered the most effective devices for RPE in young patients because they produce therapeutic effects that are not only limited to the correction of crossbite or the increase in arch width [5, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Occlusal acrylic splints are considered the most effective devices for RPE in young patients because they produce therapeutic effects that are not only limited to the correction of crossbite or the increase in arch width [5, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Mandibular displacement is more controversial, keeping in mind that the mandible is the dynamic part of the dentofacial structures. Some authors reported an anterior mandibular displacement, which improved class II malocclusion, either through dental casts studies [25] or by cephalometric evaluation [20]. The "foot and shoe" theory and the "spontaneous correction of class II malocclusion" phenomenon were introduced [26].…”
Section: Introductionmentioning
confidence: 99%